Scale of Attitudes Towards Research (EACIN-R): Psychometric Properties in Peruvian University Students - Hidalgo Euribe, Juana Patricia (2023)
The objective of this instrumental research was to confirm the psychometric properties of the EACIN-R Attitudes towards Research Scale, which contains three factors with 28 items comprised in three subscales: interest, vocation and assessment of research. 220 students from a Peruvian university participated, 82 men and 138 women. Confirmatory factor analysis and parallel Horn analysis confirmed the internal structure of the instrument, the trifactorial model, and the number of items in each subscale. Cronbach's alpha index, for the reliability analysis, yielded a value of .898 in the total test. In addition, reliability was obtained for each of its factors, vocation (.862), assessment (.692) and interest in research (.757). It is concluded that the instrument presents a good level of internal consistency, and its use is supported to measure this construct in university students with similar characteristics to the participants in this study.